En quête de statut. Mobilités et mobilisations des demandeurs d’asile soudanais en Égypte et en Israël, 1995-2015 - Pauline Brücker (Les Cahiers d’EMAM)
At the crossroads of the sociologies of exile, migration policies and social mobilizations, this thesis analyzes the phenomenon of refugees without asylum, and their quests for status which unfold in time and space. By analyzing this issue from the case study of Sudanese exiles turning around and waiting in the Nile region between Egypt and Israel in quest for a statuts, this thesis observes the impacts of exclusion practices and borders on social and political trajectories of exiles. By demonstrating, resisting, waiting and migrating elsewhere and beyond borders, exiles deploy various aspects of their agency to adapt to the different forms of exclusion they encounter, searching ways towards a better future. The quest of status phenomenon studied here thus appears perpetually fueled by two opposing forces, explaining therefore its perpetuation over time and space : modes of exclusion which illegalize and make migrants more vulnerable on the one hand; on the other, multiple forms of resistance deployed to counter the exclusions suffered.